Effect of different media on growth and physiological traits of oil palm seedlings in hyplug tray and polybag - Mohamad, Nurul Hashikin (2015)
Good planting medium is essential for enhancement of excellent drainage, aeration and root establishment of oil palm seedlings in nursery. Combination of agricultural by-product such as coco peat with bio-organic fertilizer can be used to improve soil structures of planting medium. Hyplug tray was introduced with unique basic features to overcome the flooding and environmental problem in order to maintain the growth performance of oil palm seedlings at pre-nursery stage. The objectives this study are to identify the best combination of planting medium for oil palm seedlings growth in pre-nursery stage, to compare the effectiveness of using Hyplug tray and polybag growth container and, to evaluate growth and physiological characteristics performance of FELCRA D×P planting materials. This study was conducted at FELCRA Tebing Tinggi, Segamat, Johor using a split-split plot design with 4 replications. Two types of growth containers, namely Hyplug tray and polybag assign as a main plot. Four planting media were used as a sub- plot, M1 (top soil) as a control, M2 (topsoil + coco peat, 1:1 ratio), M3 (topsoil + 50g FELCRA Bio-Organic NRich) and M4 (topsoil + coco peat, 1:1 ratio + 50g FELCRA Bio-Organic NRich) and the sub-sub plot was four different FELCRA D×P crosses. Data on vegetative growth traits such as plant height, fronds length, number of fronds, fresh and dry weight of seedlings was measured. Leaf area, root length, chlorophyll content and nutrients concentrations was analysed using a root scanner, LI-3100 leaf area meter, SPAD 502 chlorophyll meter and autoanalyzer, respectively. From this study, it was observed that the treatments applied were significantly effects on growth and physiological traits of oil palm seedlings at pre-nursery stage.